The Rising Cost of Ambient Air Pollution thus far in the 21st Century Results from the BRIICS and the OECD Countries - Roy, Rana (OECD Publishing, 2017)
This paper presents updated results for the cost of ambient air pollution in 41 countries: the 6 major emerging economies known as the BRIICS - Brazil, Russia, India, Indonesia, China and South Africa - and the 35 member-countries of the OECD. It draws on the epidemiological evidence base assembled in the Global Burden of Disease Study 2015, in order to detail results for mortalities from ambient air pollution (AAP) - ambient particulate matter pollution (APMP) and ambient ozone pollution (AOP) - in each of these 41 countries, at successive five-year intervals from 2000 to 2015
Keywords: Environment